2016
DOI: 10.1016/j.msard.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Brain health: time matters in multiple sclerosis

Abstract: The consensus findings of an international author group recommend a therapeutic strategy based on proactive monitoring and shared decision-making in MS. Early diagnosis and improved treatment access are also key components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
291
2
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 335 publications
(318 citation statements)
references
References 271 publications
(385 reference statements)
3
291
2
22
Order By: Relevance
“…5,10 Our results point towards the importance of starting effective DMT treatment early with stepwise escalation as needed, both from a clinical and a health economic perspective. 13 Although no causality can be shown in this study, ReMuS has shown that production losses are low in patients with early active MS and effective DMT therapy. 4 The challenge remains, however, to show how production losses and informal care -that is, costs outside the healthcare system -are better controlled by delaying disability progression.…”
Section: Discussionmentioning
confidence: 57%
“…5,10 Our results point towards the importance of starting effective DMT treatment early with stepwise escalation as needed, both from a clinical and a health economic perspective. 13 Although no causality can be shown in this study, ReMuS has shown that production losses are low in patients with early active MS and effective DMT therapy. 4 The challenge remains, however, to show how production losses and informal care -that is, costs outside the healthcare system -are better controlled by delaying disability progression.…”
Section: Discussionmentioning
confidence: 57%
“…This suggests that once neurodegeneration is triggered within a neural circuit, probably through innate immune activation, it may no longer respond to the therapies that halt the relapses that trigger the damage (Compston and Coles, 2002, Giovannoni et al, 2017, Hampton et al, 2013). This neurodegenerative process is detectable from the initial attacks (De Stefano et al, 2010, Giovannoni et al, 2017), but clinical progressive deterioration may only become noticed once the compensating neural reserve within affected pathways become exhausted (Giovannoni et al, 2016a, Giovannoni et al, 2017). This can occur early as in primary progressive MS or following a number of attacks in secondary progressive MS (progressive worsening following a period of relapsing attacks) (Compston and Coles, 2002, Giovannoni et al, 2016a, Lublin et al, 2014).…”
Section: Inflammatory and Neurodegenerative Disease In Msmentioning
confidence: 99%
“…This neurodegenerative process is detectable from the initial attacks (De Stefano et al, 2010, Giovannoni et al, 2017), but clinical progressive deterioration may only become noticed once the compensating neural reserve within affected pathways become exhausted (Giovannoni et al, 2016a, Giovannoni et al, 2017). This can occur early as in primary progressive MS or following a number of attacks in secondary progressive MS (progressive worsening following a period of relapsing attacks) (Compston and Coles, 2002, Giovannoni et al, 2016a, Lublin et al, 2014). Importantly, this argues for early and effectively treatment to maintain brain health (Giovannoni et al, 2016a).…”
Section: Inflammatory and Neurodegenerative Disease In Msmentioning
confidence: 99%
“…The development of new criteria leading to earlier diagnosis 8,9 and initiatives arguing for early diagnosis and early effective intervention to preserve brain loss reinforces this approach. 10 This raises, however, the question of the value to society of this early investment of public funds in view of the high cost of treatment, and this question can only be answered in the long term. In diseases such as MS, prevalence costs (i.e.…”
Section: Introductionmentioning
confidence: 99%